Coral Bleaching Patterns, Processes, Causes and Consequences (Ecological Studies, Analysis and Synthesis,, 2018)
One of the most serious consequences of global climate change for coral reefs is the increased frequency and severity of mass coral bleaching events and, since the first edition of this volume was published in 2009, there have been additional mass coral bleaching events. This book provides comprehensive information on the causes and consequences of coral bleaching for coral reef ecosystems, from the genes and microbes involved in the bleaching response, to individual coral colonies and whole reef systems. It presents detailed analyses of how coral bleaching can be detected and quantified and reviews future scenarios based on modeling efforts and the potential mechanisms of acclimatisation and adaptation. It also briefly discusses emerging research areas that focus on the development of innovative interventions aiming to increase coral climate resilience and restore reefs.